Placental Thickness and Its Correlation with Gestational Age: A Cross-sectional Ultrasonographic Study - Acharya, Sumnima; Tiwari, Awadesh; Sharma, Rupesh (Journal of Lumbini Medical College, 2018)
Introduction: Placenta grows in size with the advancement of gestational age (GA) and plays an important role for delivery of nutrients from mother to fetus. Ultrasonography (USG) is implicated for the estimation of GA by using fetal growth parameters like Femur Length (FL), Bi-parietal Diameter (BPD), Head Circumference (HC), and Abdominal Circumference (AC). This study intends to observe the correlation between Placental Thickness (PT) and GA. Methods: It was an observational, cross-sectional, and analytical study conducted over a period of six months from November 2017 to April 2018. Fetal growth parameters i.e. FL, BPD, HC, and AC were measured to estimate GA. PT was also measured at the same time. Results: There was a positive correlation between PT and GA (r = 0.89, n=249, p < 0.001). Pearson correlation coefficient between the two variables at second and third trimesters were 0.81 and 0.49 respectively. Fisher r-to-z transformation was used to analyze the difference between those two coefficients and was found to be statistically significant (z = 4.6, p < 0.001). This indicates that there was a significant overall relationship between PT and GA. As GA increases, PT also increases. Conclusion: Our study observed a positive correlation between the PT and GA in second and third trimesters. Thickness of placenta can thus be used as a reliable parameter for the estimation of GA during the second and third trimesters, and can be used as a supplementary USG parameter along with FL, BPD, HC and AC. DOI: https://doi.org/10.22502/jlmc.v6i2.214